Bootstrap DEA Efficiencies of the GCC Islamic Banks: Sources and Comparison During 2014-2016 - Samad, Abdus (International Journal of Economics and Financial Issues, 2021)
This paper, first, obtained three categories of efficiencies, overall bias-corrected technical efficiency (OTEBC), bias-corrected pure technical efficiency (PTEBC) and bias-corrected scale efficiency (SE) of the Islamic banks of the Gulf Cooperating Countries (GCC) during 2014-216 using the bootstrap Data envelopment Analysis(DEA). Second, decomposing the overall bias-corrected technical efficiency (OTEBC) the paper found the bias-corrected pure technical efficiency (PTEBC) and the bias-corrected scale efficiency (SE) were 91 percent and 59.8 percent respectively and thus PTEBC dominated the OTBBC (82.4 percent) and the SE (59.8 percent) of the GCC Islamic banks. Third, the paper found the sources of the inefficiency of the Islamic banks of the GCC was the DRS. Except the Islamic banks of Qatar, banks of the GCC countries were inefficient either because they operated under the IRS or DRS. DRS was the major source of inefficiency. Qatar Islamic banks demonstrated the highest level of efficiency in all three efficiency among GCC. The paper provides suggestions for future study. Keywords: GCC Islamic Banks, Technical efficiency, Bootstrap DEA, Bias-corrected technical efficiency. JEL Classifications: C14, G21; G22 DOI: https://doi.org/10.32479/ijefi.10127